Intellectual virtue perspectives from ethics and epistemology - DePaul, Michael R. (Michael Raymond), 1954-; Zagzebski, Linda Trinkaus, 1946- (Oxford : Clarendon, 2003)
Virtue ethics has attracted a lot of attention and there has been considerable interest in virtue epistemology as an alternative to traditional approaches in that field. This book fills a gap in the literature for a text that brings virtue epistemologists and virtue ethicists together.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Virtue; Virtue epistemology